O manejo extrativista influencia a dinâmica do carbono e nutrientes em carnaubais nativos? - Amaral, Ruan Veras do (2023)
Anthropogenic action can negatively or positively impact the landscape behavior of plant communities. In the Brazilian Northeast, one of the region's most characteristic activities, the extraction of Copernicia prunifera (Miller) HE Moore or popularly known as Carnaúba, is an example of extractivism, occurring mainly in traditional communities, as a source of livelihood for countless families. People involved in carnauba management visually verified that cutting the leaves leads to more intense vegetative growth in the palm trees. From this observation, the hypothesis was raised that carbon sequestration by managed Copernicia prunifera (Miller) HE Moore individuals is superior to carbon sequestration by unmanaged individuals. The general objective of the study was to evaluate the influence of extractive activity on carbon sequestration, nutrient stocks and biomass production in native carnauba ecosystems. To achieve this objective, biomass production, export of biomass and nutrients through extractivism and carbon stock and soil fertility were evaluated under and outside the influence of managed and unmanaged palm trees. The study was carried out in a completely randomized design and the data were subjected to analysis of variance, mean comparison test (Tukey) and tests of the assumptions of homogeneity of variances and normal distribution of errors. The extractive management of removing carnauba leaves has a low capacity to export carbon and nutrients. Since the influence of this management has the capacity to stimulate the production of leaves by carnauba plants and is likely to stimulate the production and deposition of biomass from other plants present in the system, since the area without direct influence of the carnauba plant presented a higher concentration of carbon in the soil in the managed unit. Carnaúba proved to be a carbon storage compartment as important as the soil. The density of native carnauba forests and reforestation has important potential for carbon sequestration.